2015
DOI: 10.1039/c4cp05508j
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-exchange mechanism: new insight into solid-phase extraction of uranium based on a combined experimental and theoretical study

Abstract: In numerous reports on selective solid-phase extraction (SPE) of uranium, the extraction of uranium is generally accepted as a direct coordination of the ligands on the solid matrix with the uranyl, in which the critical effect of the hydration shell on the uranyl is neglected. The related mechanism in the extraction process remains unclear. Herein, the detailed calculation of activation energy and the geometry of the identified transition states reveal that the uranium extraction by a newly-synthesized urea-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…5a)2829. The complex formation is an exchange process in essence between the glutarimidedioxime and the coordinated water molecules in the first hydration shell of the Mn(II)30. The most practical solvation model should comprise the explicit inclusion of waters in the first hydration shell combined with continuum solvation model for the remainder of the hydration shell31.…”
Section: Resultsmentioning
confidence: 99%
“…5a)2829. The complex formation is an exchange process in essence between the glutarimidedioxime and the coordinated water molecules in the first hydration shell of the Mn(II)30. The most practical solvation model should comprise the explicit inclusion of waters in the first hydration shell combined with continuum solvation model for the remainder of the hydration shell31.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, solid‐phase extraction as an auxiliary method for enhanced efficiency of the PUREX process should be in line with the goal pursued by the aqueous reprocessing process of spent nuclear fuel. Unfortunately, the interactions between solid‐phase extractants (such as, hydrothermal carbon, porous organic polymers, metal‐organic frameworks (MOFs), porous silica, graphene) and metal ions reported so far are mostly chemical adsorption (coordination/complexation by functional groups) and physical adsorption (trapping via pores/channels, or van der Waals adsorption) or both . Chemical adsorption is mainly based on coordination interaction between electron‐rich (donor) atoms, such as O/N/S, and electron‐deficient metal cations, but at higher acidity (usually pH<2), the separation effect will be lost due to the protonation of ligands .…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, the peaks of mGO-PAO became wider and shifted to higher binding energy after adsorption of U(VI), which is consistent with the result reported in the literature. 55,56 On the basis of the XPS analysis, it can be concluded that the U(VI) was adsorbed onto mGO-PAO through the complexation of U(VI) with the imine and the hydroxyl, which probably is due to the η 2 chelation, 57,58 as shown in Figure 14. The results of XPS analysis also indicated the successful preparation of mGO-PAO.…”
Section: Effect Of Temperature and Thermodynamicmentioning
confidence: 97%